1998
DOI: 10.1258/1357633981931254
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with realtime teledermatology in Northern Ireland

Abstract: Teledermatology consultations were organized between two health centers and two hospitals in Northern Ireland using low-cost videoconferencing equipment. A prospective study of patient satisfaction was carried out. Following each teleconsultation, patients were asked to complete a questionnaire assessing their satisfaction with the service. Over 22 months, 334 patients were seen by a dermatologist over the video-link, and 292 patients (87%) completed the 16-item questionnaire. Patients reported universal satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 0 publications
6
77
0
1
Order By: Relevance
“…A review of the current clinical literature indicates that experiences with using various applications of telemedicine for somatic consultations are overwhelmingly positive (Allen & Hayes, 1995;Loane et al, 1998;Mekhjian et al, 1999;Pedersen & Holland, 1995), while experiences with conducting remote mental health services yield varying results. Of particular interest are findings that indicate that psychologists tend to be more apprehensive about this technology than are their patients in treatment.…”
Section: Opinions About Telemedicinementioning
confidence: 99%
“…A review of the current clinical literature indicates that experiences with using various applications of telemedicine for somatic consultations are overwhelmingly positive (Allen & Hayes, 1995;Loane et al, 1998;Mekhjian et al, 1999;Pedersen & Holland, 1995), while experiences with conducting remote mental health services yield varying results. Of particular interest are findings that indicate that psychologists tend to be more apprehensive about this technology than are their patients in treatment.…”
Section: Opinions About Telemedicinementioning
confidence: 99%
“…Patients reported that they were equally satisfied with LI teledermatology and conventional care and had no strong preference for one modality over another (Whited, 2010). Some patients reported initial discomfort due to the presence of camera (Gilmour et al, 1998;Loane et al, 1998a). Relatively few studies evaluated referring provider satisfaction in LI teledermatology.…”
Section: Satisfaction With Live Interactive Teledermatologymentioning
confidence: 99%
“…This allows direct interaction between the patient and the consultant. Loane et al showed that the colour and temporal resolution of live video images could be improved by changing from a hand-held single-chip video camera to a tripod mounted three-sensor RGB (red, green, blue) chip camera (13).…”
Section: Video Imaging Requirementsmentioning
confidence: 99%
“…Without the direct communication between the dermatologist and patient that real time interactive technology allows, it is up to the referring clinician to relay the dermatologist's recommendations to the patient. In addition to affecting patient satisfaction, this may influence the referring clinician's satisfaction as well (7,8,(15)(16)(17)(18).…”
Section: Video Imaging Requirementsmentioning
confidence: 99%